TRANSFORMATION OF LOAN ACTIVITIES OF A COMMERCIAL BANK TO DIGITALIZATION - Baymagambet Nursultan Zhanatuly; Salzhanova Zaure Abildinovna; Kenges Gulzhihan Kengeskyzy; Abdikarimova Aliya Toleutaevna; Omarkhanova Zhibek Maksutovna (Academic Journal of Physical and Chemical Sciences, 2020)
Currently, digital transformation is seen as an integral element of maintaining the competitiveness of banks: on average, a third of banking operations are already carried out using digital technology. The widespread adoption of digital technology is associated with the needs of society, which at the present stage of innovation development is aware of all the advantages achieved through the use of technology in the banking sector. In conclusion, we note that the digital transformation process should be based on a digital strategy developed taking into account the characteristics and needs of a particular bank. The implementation of a rational digital transformation strategy will allow individual banks, and subsequently the entire banking sector, to increase business efficiency and enter a new stage in the development of financial and credit organizations and the economy as a whole. Currently, the financial system is in the process of development in accordance with the modern requirements of the digital economy.